End-Wenlock terminal Mulde carbon isotope excursion in Gotland, Sweden: Integration of stratigraphy and taphonomy for correlations across restricted facies and specialized faunas - Jarochowska, Emilia; Bremer, Oskar; Pröpster, Stephanie; Heidlas, Daniel; Vandenbroucke, Thijs R.A.; Munnecke, Axel (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The decline of the upper peak of the Homerian Mulde carbon isotope excursion (CIE) is used in low- to mid-paleolatitudes as a marker for the Wenlock/Ludlow boundary, which is otherwise difficult to constrain in carbonate successions. In the Midland Platform (England) the CIE ends just below the boundary or ranges through it, whereas in Baltic sections it has been placed substantially below the inferred base of the Ludlow Stage. Difficulties in correlating the Baltic sections are caused by widespread development of lagoons and sabkhas with specialized conodont and vertebrate faunas. We describe here a lagoonal section from Gothemshammar, eastern Gotland (Sweden), spanning the entire upper peak of the Mulde CIE. Based on integrated conodont, δC and sequence stratigraphy, a hardground present at the lowering limb of the CIE is correlated with a sequence boundary present across the Baltic Basin, in the Midland Platform, and the southern shelf of Laurentia. This sequence boundary corresponds to a global eustatic regression and can serve as a correlative horizon in restricted facies with depauperate or specialized fauna. The Wenlock-Ludlow boundary is placed in the transgressive strata overlying this boundary. Species richness and abundance of thelodonts, anaspids, and osteostracans at Gothemshammar represent one of the first diversity peaks of vertebrates in the Silurian. Associated conodonts are characteristic for late Wenlock marginal-marine environments and distinguished by large, robust elements. We quantitatively assess the conodont assemblages to evaluate to which degree the overrepresentation of large elements in these facies is produced by taphonomic processes. The taphonomic alteration differs between species and facies, but is lowest for the shallow-water specialist Ctenognathodus murchisoni. Regardless, the use of this species as an index taxon is discouraged based on its strong facies affinity. Instead, the integrated approach proposed here indicates that the Wenlock/Ludlow boundary is situated lower in the Baltic sections than previously identifie
Keywords: Conodont; Deformation; Fish; Palynomorph; Taphonomy; Vertebrate